Unlocking and Sharing Data in Astronomy. - Henneken, Edwin (Bulletin of the Association for Information Science & Technology)
The astronomy community has been a leader in efforts to preserve and share research data to facilitate ongoing discoveries. Since some efforts have led to isolated and abandoned websites, the need to deposit data in specifically designed and maintained repositories is now recognized. These repositories may apply persistent data identifiers to data products including large and small datasets, software and raw data throughout the research cycle. Researchers should be encouraged to deposit and share data, but guidelines and practices are inconsistent and publishers' policies vary. Agreement among stakeholders must be found on clearly defined standards for data citation and linking through publications. Establishing and complying with citation standards for all related data products will promote data discovery and reuse.